2022
DOI: 10.1002/vms3.724
|View full text |Cite
|
Sign up to set email alerts
|

The medication violations in racehorses at Louisiana racetracks from 2016 to 2020

Abstract: Introduction/Background: The number of publications for most common drug violations in racehorses is limited. This study reports the most common medication violations in racehorses at four major racetracks in Louisiana between 2016 and 2020.Methods: During this 5-year period, 27,237 blood samples and 25,672 urine samples collected during the course of normal race meeting activities were analysed by initial screening procedure utilizing Liquid Chromatography Mass Spectrometry (LC-MS/MS). Following initial scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…While the authors stated that medication violations in racehorses in Louisiana represented 1% of the total number of samples analyzed, only postrace racehorse blood and urine samples were analyzed for testing. 26 Significantly, these results correlate well with the same 2 drugs detected in contaminated horsemeat by food safety organizations.…”
Section: Horsemeat Food Safety and Public Health Risksupporting
confidence: 68%
See 1 more Smart Citation
“…While the authors stated that medication violations in racehorses in Louisiana represented 1% of the total number of samples analyzed, only postrace racehorse blood and urine samples were analyzed for testing. 26 Significantly, these results correlate well with the same 2 drugs detected in contaminated horsemeat by food safety organizations.…”
Section: Horsemeat Food Safety and Public Health Risksupporting
confidence: 68%
“…24 Lasix (furosemide), a diuretic, is another drug administered to horses on race day to reduce the risk of hemorrhage in the lungs. 25 In a recent study, 26 over 50,000 blood and urine samples from racing thoroughbreds and racing Quarter Horses, the number one horse sent to slaughter from the United States, were analyzed postrace from all 4 racetracks operating in the state of Louisiana from 2016 to 2020. Results showed that phenylbutazone with or without other drugs and clenbuterol (a sympathomimetic amine bronchodilator) were the most common drugs detected in thoroughbred and Quarter Horse racehorses.…”
Section: Horsemeat Food Safety and Public Health Riskmentioning
confidence: 99%
“…Typically, veterinary surgeons were accused of providing excessive and occasionally inappropriate medications rather than illegal medications. The challenge of treating horses under governing body regulations is highlighted by the papers showing that most medication violations were for illegal levels of prescription therapeutic medications in contravention of established thresholds and/or withdrawal guidelines 3,50 …”
Section: Resultsmentioning
confidence: 99%
“…The challenge of treating horses under governing body regulations is highlighted by the papers showing that most medication violations were for illegal levels of prescription therapeutic medications in contravention of established thresholds and/or withdrawal guidelines. 3,50 The use of intra-articular medications was another key area of concern, 7,29,32 with excessive repeat administrations cited as problematic. 32 Furthermore, it was suggested that 'maintenance joint injections were now expected' by trainers/owners.…”
Section: Confidentialitymentioning
confidence: 99%
“…Taddei et al (2011) reported positivity in 0.45% of samples collected from race horses in Illinois over a 5 year period. Waller et al (2022) found 1.01% positive samples out of 27,237 blood and 25,672 urine samples collected at Loussiana racetracks from 2016 to 2020. On the Of the substances detected during the period under review, caffeine, morphine, theobromine and oripavine may occur naturally in some plants.…”
Section: Discussionmentioning
confidence: 98%